Addressing Load balancing Issues Related to Elastic Cloud Using Biomimetic Algorithms (2015)
In business world, competitors use innovative approaches to improve their performance and profits. Cloud computing is one of these innovative approaches that have Allowed many companies to further take advantage of their potential. Cloud computing is assisting companies to execute their business plans more efficiently, thus providing them with an advantage over their competitors. Despite the benefits that cloud could offer, various challenges exist in this field. Load balancing and cloud performance are two examples of such challenges. This paper aims to discuss some of these challenges and how biomimetic algorithm could be employed to address them. Our approach is inspired by load regulation occurring in nature; more precisely, in human body.